Plant regeneration from seedling explants of common bean : Phaseolus vulgaris L. - Ahmed, E. Eissa; Bisztray, György Dénes; Velich, István (Acta Biologica Szegediensis, 2002)
For shoot induction and plant regeneration in bean we used MS media+BA and NAA. Multiple shoot induction was obtained in case of P. vulgaris cv. Fônix and Maxidor. The efficiency of regeneration from intact seedling (IS) and cotyledonary node (CN) explants was compared. The optimum treatment for the induction of multiple shoot formation was the culturing of (IS) on MS-based media+BA and NAA. Multiple shoot induction on dry bean (CN) cultured on full MS medium+1mg/l BA and 0.1mg/l NAA was feasible. Shoots that were 2cm in length or longer and having 2 trifoliate leaves were responsible for rooting ability, and root development. The method can be applied in transformation experiments.